2022
DOI: 10.3389/fpls.2022.820767
|View full text |Cite
|
Sign up to set email alerts
|

The Necrotroph Botrytis cinerea BcSpd1 Plays a Key Role in Modulating Both Fungal Pathogenic Factors and Plant Disease Development

Abstract: Botrytis cinerea is a necrotrophic microbe that causes gray mold disease in a broad range of hosts. In the present study, we conducted molecular microbiology and transcriptomic analyses of the host–B. cinerea interaction to investigate the plant defense response and fungal pathogenicity. Upon B. cinerea infection, plant defense responses changed from activation to repression; thus, the expression of many defense genes decreased in Arabidopsis thaliana. B. cinerea Zn(II)2Cys6 transcription factor BcSpd1 was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…It induces host defense to promote host cell death using cell death-inducing proteins and toxins to trigger plant cells necrosis (Bi et al ., 2021; Leisen et al ., 2022). However, it was demonstrated that the BcSpd1 Zn(II) 2 Cys6 transcription factor is a potential suppressor of plant defense at an early stage (14 hpi) of A. thaliana infection by B. cinerea (Chen et al ., 2022). In this study, we show that BcLysM1 can reduce plant immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…It induces host defense to promote host cell death using cell death-inducing proteins and toxins to trigger plant cells necrosis (Bi et al ., 2021; Leisen et al ., 2022). However, it was demonstrated that the BcSpd1 Zn(II) 2 Cys6 transcription factor is a potential suppressor of plant defense at an early stage (14 hpi) of A. thaliana infection by B. cinerea (Chen et al ., 2022). In this study, we show that BcLysM1 can reduce plant immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Botrytis cinerea, Alternaria brassicicola, and Neopestalotiopsis sp. (Figure 3B) are species commonly related to the necrotrophic strategy as they have a molecule pool with a high destructive power of the plant's tissues from the first time of the interaction with the host plant [46][47][48]. Finally, hemibiotrophic fungi have the capacity to combine both biotrophic and necrotrophic strategies [49].…”
Section: Photosynthetic Alterations By Pathogen Infectionmentioning
confidence: 99%
“…Many reports on fungal effectors stem from interactions between the pathogen and host; these reports have revealed effectors during appresorium formation and development [9,[14][15][16], in biotrophy [17][18][19], and in necrotrophy stages [20][21][22][23][24]. It is known that many effectors are specific to a particular stage during the pathogen-host interaction.…”
Section: Introductionmentioning
confidence: 99%